The anticancer drug ellipticine is an inducer of rat NAD(P)H:quinone oxidoreductase - Stiborová, Marie; Dračínská, Helena; Svášková, Dagmar; Hodek, Petr; Hudeček, Jiří; Ryšlavá, Helena; Schmeiser, Heinz H; Frei, Eva (Collection of Czechoslovak Chemical Communications, 2007)
The antineoplastic agent ellipticine was investigated for its ability to induce the biotransformation enzyme NAD(P)H:quinone oxidoreductase (DT-diaphorase, EC 1.6.99.2) in male Wistar rats. Using the real-time polymerase chain reaction, the levels of NAD(P)H:quinone oxidoreductase mRNA were determined in livers, kidneys and lungs of rats treated intraperitoneally with ellipticine (40 mg/kg body weight) and of control (untreated) rats. Cytosolic fractions were isolated from the same tissues of control and ellipticine-treated rats and tested for NAD(P)H:quinone oxidoreductase protein expression and its enzymatic activity. The results demonstrate that ellipticine is a potent inducer of NAD(P)H:quinone oxidoreductase in rat livers and kidneys, while no induction of this enzyme was detectable in rat lungs. The increase in levels of NAD(P)H:quinone oxidoreductase mRNA correlates with the increase in expression of its protein and enzymatic activity, measured with menadione and 3-nitrobenzanthrone as substrates. The results, the identification of the potential of ellipticine to induce NAD(P)H:quinone oxidoreductase, suggest that this drug is capable of modulating biological efficiencies of the toxicants and/or drugs that are reductively metabolized by this enzyme.
Keywords: finanční podpora výzkumu jako téma; Enzyme Induction; enzymová indukce; Research Support as Topic; Antineoplastic Agents; Ellipticines; protinádorové látky; Quinone Reductases; elipticiny; chinonreduktasy